Dual-responsive carboxymethyl cellulose/dopamine/cystamine hydrogels driven by dynamic metal-ligand and redox linkages for controllable release of agrochemical. (1st February 2021) - Guo, Tianyu; Wang, Wangxia; Song, Junlong; Jin, Yongcan; Xiao, Huining
Highlights: Dual responsive hydrogels via disulfide and metal-catechol bonds were fabricated. Hydrogels displayed reversible sol-gel transitions with either pH or redox changes. Release of agrochemicals can be further promoted under co-triggered conditions. The results of FEM simulation are consistent with those detected in the hydrogels. Abstract: The utilization of agrochemicals in crop production is often inefficient due to lack of appropriate carriers, raising in the significant concerns of ecological environment and public health. To enhance the efficiency of agrochemical delivery, a novel cellulose-based hydrogel was constructed in this work by cross-linking dopamine (DA)-modified carboxymethyl cellulose (CMC) with cystamine (CYS) in the presence of Fe 3+ ions. The hydrogels displayed reversible sol-gel transitions upon exposure to stimulation of changes in pH and redox, leading to the controllable release of model agrochemical (6-benzyladenine). Compared with single-triggered condition, the hydrogel doubled the cumulative release when co-triggered by pH and redox. The dynamic metal/catechol complexation and disulfide bonding coexist in the hydrogel networks, enabling occurrence of dynamic reaction under a variety of environmental conditions. The finite element method (FEM) was employed to simulate the hydrogel to provide a theoretical insight into the tested drug delivery. Benefitting from the reversibly cross-linked networks and the excellent biodegradability of the hydrogels, we anticipate that this dual-responsive, polysaccharide-based hydrogel will offer diverse applications to reach the full potential in sustainable advancement of crop production.